The Effect of Executive Function Load on Reaction Time in E-Sports Players. - DEMİRCİ, Serdar; YILMAZ, Sudenaz; BERBEROĞLU, Utku; DEMİRCİ, Cevher; AKTAŞ, Arda; NUMANOĞLU AKBAŞ, Ayşe (Balikesir Health Sciences Journal / Balıkesir Sağlık Bilimleri Dergisi, 2026)
Objective: This study examined the effect of executive function load on reaction time in e-sports players and compared their performance with an age-matched control group. Materials and Methods: This cross-sectional controlled study included 30 competitive e-sports players and 30 healthy age-matched controls. Reaction time was assessed using the BlazePod system under four conditions: simple reaction time (SRT), choice reaction time (CRT), motor dual-task reaction time (MDRT), and cognitive dual-task reaction time (CDRT). Group differences were analyzed using independent samples t-tests. A 2 × 4 mixed-design ANOVA was conducted with group (e-sports vs. control) as the between-subject factor and task condition as the within-subject factor. Bonferroni-adjusted post hoc tests were applied where appropriate. Results: E-sports players demonstrated significantly shorter reaction times than controls in all conditions: SRT (291.5±67.3 vs. 413.4±94.1 ms, p<0.001), CRT (443.3±173.6 vs. 618.4±199.3 ms, p<0.001), MDRT (446.4±115.0 vs. 616.2±251.6 ms, p=0.001), and CDRT (490.9±183.4 vs. 622.3±223.8 ms, p=0.016). A significant main effect of task condition was observed (F(3,174)=31.726, p<0.001), while the group × task interaction was not significant (F(3,174)=0.641, p=0.590). Post hoc analysis showed that SRT was significantly shorter than all other conditions (p<0.001), with no differences among dual-task conditions. Error rates did not differ between groups (p>0.05). Conclusion: E-sports players exhibited shorter reaction times than controls across all conditions. Increased task load prolonged reaction time similarly in both groups.